An Analytical Review Of The Relationship Between Dispatching Rules And Performance For Dynamic Scheduling In An Identical Parallel Machine Environment - Jusoh, Zuraidah (Universiti Sains Malaysia, 2005)
This report consist an analytical review of the relationship between dispatching rules and performance measure for dynamic scheduling problem. The review is focused on an identical parallel machine environment. The dynamic issues that considered are machine breakdown and operator absent. The main objective of the research work is to analyze the performance of dispatching rules against different performance measures. Five suitable dispatching rules that considering the priority of weighs which called weighted dispatching rules is used. Dispatching rule is used to specify which job should be selected for work next from among a queue of jobs. Simulation model is developed based on real world case study using WITNESS software. Than the experiment model is developed by adding disturbance parameter likes machine breakdown and operator absent. The experiment is done to determine the effects of the disturbance parameter to the performance of dispatching rules used. The experiment result is proved by analysis of variance (ANOVA). From the experiment analysis, the different dispatching rules provide the different result of performance measures. Dispatching rules can be used to determine the minimum throughput time, minimum lateness and earliness of the jobs. The performance of dispatching rules also depends on disturbance parameter that used in the experiment model and the quantity of jobs required.